EFFECT OF MUTAGEN ON SOMATIC EMBRYOGENESIS AND PLANT REGENERATION OF LOCAL AROMATIC RICE CV. “DUBRAJ” - SWAIN, SUDHANIRJHARINI; C. SAMAL , KAILASH; K. TRIPATHY, SWAPAN (The Bioscan, 2023)
Establishment of an efficient in vitro protocol via somatic embryogenesis is an essential prerequisite in harnessing the advantage of cell and tissue culture for genetic improvement in aromatic indica rice. Besides, the present investigation was undertaken to develop an efficient in vitro mutagenesis system with early callus induction and rapid plant regeneration in a popular aromatic rice variety Dubraj. The maximum embryogenic calli (90%) with excellent callus growth was acchieved in MS medium supplemented with 2.5mg/l of 2, 4-D + 0.5mg/L Kn. Such calli on transfer to MS + 2.5 mg/l BAP and 1.0 mg/l NAA resulted maximum morphogenetic response (86%) with production of well developed green plantlets after two weeks of culture. However, addition of EMS (0.005%) to the above medium still maintained optimum callus growth and regeneration of green plantlets although with reduced callusing (47%) and regeneration response (62.0%). Such a regeneration system can be routinely used for isolation of desirable in vitro mutants for aromatic rice breeding.